Surgical Cavity in Extended Endoscopic Endonasal Approach to the Skull Base and their Relationship with Cerebrospinal luid Leak (Global Journal of Medical Research, 2023)
Cerebrospinal fluid leak represents a fearsome complication after Extended Endoscopic Endonasal Approach to the skull base A descriptive observational study was performed in 550 patients operated for skull base tumors through Extended Endoscopic Endonasal Approaches between 2010 and 2021 at the Ameijeiras Hospital Surgical cavity was classified according to relation with intracranial hydrodynamic system into type 0 no contact with the hydrodynamic system type 1 subarachnoid cavity type 2 cisternal cavity and type 3 ventricular cavity A significant increase CSF leak incidence was determined in type 2 10 8 and type 3 18 cavity and it was associated to increment of hydrodynamic energy secondary to Bernoulli laws
Keywords: extended endonasal endoscopic approach (EEEA); cerebrospinal fluid (CSF) leak; surgical cavity; bernoulli laws